PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE BERBANTUAN SPESIMEN PADA MATERI INVERTEBRATA - Handayani, Dwi; Bintari, Siti Harnina; -, Lisdiana (Journal of Biology Education, 2013)
The aim of research determine difference between learning outcomes and student activity using learning model Picture and Picture assisted specimens on material Invertebrates. Research of design use one shoot case study. The sample was class X-1 and X-2 determined Total Sampling technique. The independent variable was learning model used Picture and Picture helped Invertebrates specimens, while dependent of variable was learning outcomes (LKS score and final exam score) and student activities. The activity student learning in classical style in class X-1 was 88% and X-2  was 86%. The cognitive learning outcomes students used  classical style in class X-1 was  93,78% and class X-2 was 88,8%. The outcomes data teacher performance in class X-1 and X-2 was very good, both classes indicated average grade of 15. The students response in class X-1 was 85.1% while in class X-2 was 93,8%. Teaching response toward method showed interest and agree using LKS models Picture and Picture helped Invertebrates specimens  appicated this study.The conclusions this study is application learning models Picture and Picture helped Invertebrates specimens method can increase activity students in classical style was 87% and student learning outcomes in classical style was 86.33% apply in senoir high school of Teuku Umar Semarang. Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar dan aktivitas siswa dengan menggunakan model pembelajaran picture and picture berbantuan spesimen pada materi invertebrata. Desain penelitian ini one shoot case study. Sampel penelitian ini yaitu siswa kelas X-1 dan X-2 yang ditentukan dengan teknik total sampling. Variabel bebas berupa model pembelajaran Picture and Picture berbantuan spesimen Invertebrata, sedangkan variabel terikat berupa hasil belajar (nilai LKS dan nilai akhir) dan aktivitas siswa. Hasil belajar kognitif siswa secara klasikal kelas X-1 sebesar 93,78% dan kelas X-2 sebesar 88,88. Aktivitas siswa secara klasikal pada kelas X-1 sebesar 88% dan X-2 sebesar 86%.. Kinerja guru pada kelas X-1 dan X-2 sangat baik. Tanggapan siswa kelas X-1 sebesar 85,1% dan kelas X-2 sebesar 93,8%. Tanggapan guru menunjukkan bahwa guru tertarik dan setuju menggunakan media LKS dengan model Picture and Picture berbantuan spesimen Invertebrata yang diterapkan dalam proses pembelajaran. Simpulan penelitian ini adalah penerapan model pembelajaran Picture and Picture berbantuan spesimen pada materi Invertebrata dapat meningkatkan aktivitas siswa secara klasikal sebesar 87% dan hasil belajar siswa secara klasikal sebesar 86,33% di SMA Teuku Umar Semarang.